The UTMOST survey for magnetars, intermittent pulsars, RRATs, and FRBs – I. System description and overview. Issue 4 (15th January 2020) - Venkatraman Krishnan, V; Flynn, C; Farah, W; Jameson, A; Bailes, M; Osłowski, S; Bateman, T; Gupta, V; van Straten, W; Keane, E F; Barr, E D; Bhandari, S; et al.
ABSTRACT: We describe the ongoing 'survey for magnetars, intermittent pulsars, rotating radio transients, and fast radio bursts' (SMIRF), performed using the newly refurbished UTMOST telescope. SMIRF repeatedly sweeps the southern Galactic plane performing real-time periodicity and single pulse searches, and is the first survey of its kind carried out with an interferometer. SMIRF is facilitated by a robotic scheduler which is capable of fully autonomous commensal operations. We report on the SMIRF observational parameters, the data analysis methods, the survey's sensitivity to pulsars, techniques to mitigate radio frequency interference, and present some early survey results. UTMOST's wide field of view permits a full sweep of the Galactic plane to be performed every fortnight, two orders of magnitude faster than previous surveys. In six months of operations from 2018 January to June, we have performed ∼10 sweeps of the Galactic plane with SMIRF. Notable blind redetections include the magnetar PSR J1622−4950, the RRAT PSR J0941−3942 and the eclipsing pulsar PSR J1748−2446A. We also report the discovery of a new pulsar, PSR J1659−54. Our follow-up of this pulsar at an average flux limit of ≤20 mJy, categorizes this as an intermittent pulsar with a high nulling fraction of <0.002.